Assessment of Feed Resources Available in Punjab State of India - Tanwar, P. S.; Verma, H. K. (Indian Journal of Animal Nutrition, 2017)
The present study was undertaken to estimate the feeds and fodder availability and demand for the existing livestock population in Punjab. The study was based on secondary data collected from different sources. The livestock population was converted in to adult cattle unit (ACU) on the basis of species, age and sex. The body weight of each ACU was considered to be 350 kg and dry matter consumption was assumed to be 2% of the body weight. The ACU in the state were 5.85 million which required 6.64, 3.32 and 4.98 million tonnes of dry fodder, green fodder and concentrates per year (dry matter basis), respectively. The livestock density in the state was 107.15 animals/Km2. The total annual availability of dry fodder was 18.71 million tonnes against requirement of 6.64 million tonnes indicating an excess of 181.79%. The overall availability of green fodder was 3.31 million tonnes which was as per requirement in the state but some districts showed deficiency of green fodder. The supply of concentrate was deficient to the tune of 55.57%. The average availability of dry fodder, green fodder and concentrate was 8.77, 1.55 and 1.04 kg per ACU per day on DM basis, respectively. Hence, excess of dry fodder may be transported to deficit areas of our country while production of concentrates and green fodder production need to be increased to reduce the cost of livestock and poultry production in the state.